Implementation of Human Resource Management in Improving Employee Performance at the Regional Drinking Water Company of Tangerang Regency - Edi , Haryono (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The purpose of this study is to examine the implementation of human resource management in improving performance at the Regional Drinking Water Company (PDAM) of Tangerang Regency. The study employs a qualitative research method to describe the practices conducted within the PDAM. Data collection techniques include interviews with selected informants, such as the Head of PDAM Tangerang Regency, the Secretary of PDAM Tangerang Regency, and PDAM staff. Data analysis focuses on planning, recruitment, job placement, training, performance evaluation, and compensation. The results reveal that human resource management at PDAM Tangerang Regency, covering planning, selection and recruitment, placement, training, performance evaluation, and compensation or rewards, has been effectively implemented.